A discriminant analysis of team cohesiveness among high-performance and low-performance elite Indian volleyball players - Verma, J. P.; Modak, P.; Bhukar, J. P.; Kumar, S. (Studies in Physical Culture and Tourism, 2012)
Aim of Study. This study investigates group cohesion among elite Indian male volleyball players. The study had two purposes; firstly, to assess the role of different parameters of team cohesiveness (Group-Task and Group-Social) among the high and low performance volleyball players; and secondly, to develop a discriminant model for classifying volleyball players into high or low performance groups on the basis of group cohesion parameters. Material and Methods. Two hundred eight male elite volleyball players from India were selected for the study. The Group Environment Questionnaire was administered to the subjects prior to the tournament and the data were obtained on four parameters: Group Integration-Task (GI-T), Group Integration- Social (GI-S), Individual Attraction to the Group-Task (IAG-T) and Individual Attraction to the Group-Social (IAG-S). On the basis of the performance of the teams forty eight samples were retained for the final study in such a manner that 24 volleyball players were from the first five teams and twenty four subjects were from the last five teams. The data was analyzed using the SPSS ver. 17.0. Results. The mean values of all the four group cohesion parameters were significantly higher among high performance volleyball players in comparison with low performance players. Further, a discriminant model was prepared to classify volleyball players into high and low performance groups on the basis of cohesion variables. A disrciminant function Z was developed (Z = -5.88 +0.11 (GI-T) +0.12 (GIS) -0.05 (IAG-T) +0.15 (IAG-S)). The attained discriminant model classified correctly 75% of the cases in the sample. Conclusions. The variable Individual Attraction to the Group-Social (IAG-S) had the highest discriminating power among the four group cohesion parameters. The discriminant function Z developed in the study classified the male volleyball players into the low performance category, if its value was positive and into the high performance category, if negative.